## Solving the Equation: 0.3(6-2y) = 4.5 - 0.7(y+9)

This article will guide you through the steps of solving the equation **0.3(6-2y) = 4.5 - 0.7(y+9)**.

### Step 1: Distribute

First, we need to distribute the constants on both sides of the equation:

**0.3(6-2y) = 4.5 - 0.7(y+9)****1.8 - 0.6y = 4.5 - 0.7y - 6.3**

### Step 2: Combine Like Terms

Next, we'll combine the constant terms and the terms with 'y' on each side of the equation:

**1.8 - 0.6y = 4.5 - 0.7y - 6.3****1.8 - 0.6y = -1.8 - 0.7y**

### Step 3: Isolate the 'y' term

We need to get all the 'y' terms on one side of the equation and the constant terms on the other side. Let's add **0.7y** to both sides:

**1.8 - 0.6y + 0.7y = -1.8 - 0.7y + 0.7y****1.8 + 0.1y = -1.8**

### Step 4: Isolate 'y'

Now, subtract **1.8** from both sides:

**1.8 + 0.1y - 1.8 = -1.8 - 1.8****0.1y = -3.6**

### Step 5: Solve for 'y'

Finally, divide both sides by **0.1** to isolate 'y':

**0.1y / 0.1 = -3.6 / 0.1****y = -36**

### Solution

Therefore, the solution to the equation **0.3(6-2y) = 4.5 - 0.7(y+9)** is **y = -36**.